Стриптиз Жар-птицы: [роман] / Дарья Донцова - Донцова Дарья Аркадьевна (Иронический детектив, 2008)
Экземпляры: ф.17 (20160209) / Инвентарный номер: 060247 / Цена: 65.00 / Авт.знак: Д 67 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6